In silico Prediction of Anti–SARS-CoV-2 Effect of Dermaseptin Peptides from Amphibian Origin: Prediction of anti–SARS-CoV-2 effect of the dermaseptin peptides - Satpathy, Raghunath (Trends in Peptide and Protein Sciences, 2020)
The novel coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has now been declared as a global pandemic by the World Health Organization (WHO). Several drug molecules have been proposed that can be used against the virus. As an alternative to effective drug molecules, the antiviral peptides have the potential for effective application to control the infectious disease. In this work, the anti- SARS-CoV-2 effect of dermaseptin peptide molecules produced by the skin of the frog was evaluated by using the computational method. Three numbers of antiviral dermaseptin peptides were obtained by searching the antimicrobial peptide database (APD). First, the structure prediction of peptides was done by Pep Fold 2.0 server followed by structure validation by PROCHECK program. Then, the protein-peptide docking simulations were performed using the COVID-19 docking server. The peptides’ binding affinity with the SARS-CoV-2 spike protein macromolecule was evaluated along with eight negative control peptides and human angiotensin converting enzymes 2 (ACE2). The protein-peptide docking and interaction analysis resulted in finding that dermaseptin-S9 peptide molecule was the most efficient molecule among the selected peptides with a binding energy of -331.54 KJ/mole. Hence, as a follow-up study, the dermaseptin-S9 peptide molecule can be further designed to enhance its specificity and binding affinity for its better use against the SARSCoV-2 disease. HIGHLIGHTS Three numbers of antiviral dermaseptin peptides from APD database were in silico evaluated against SARS-CoV-2 spike protein. The antiviral dermaseptin -S9 peptide showed the highest binding affinity towards the SARS-CoV-2 spike protein macromolecule. The hydrophobic property of the distributed amino acids of the derrmaseptin-9 molecule might be related to the binding affinity.